El trabajo colaborativo - Herrera Lasluisa, Jenny Magdalena (2016)
This research work contains very important aspects in relation to collaborative work, in order to diagnose its influence and impact in the inter-learning process in the apprehension of theoretical and academic content as well as in the acquisition of skills, attitudes and useful aptitudes for the integral development of students in the “Monseñor Leonidas Proaño” Educational Unit from Latacunga Canton, Cotopaxi Province. This research work was carried out based on the results of the techniques and research tools application such as: observation, interview and survey to teachers, students, administrative and service personnel, The information obtained allowed us to establish the respective conclusions and recommendations about this project; also it is included a theoretical framework where collaborative work is described, its importance, advantages and disadvantages that lead to propose solutions to the identified problem, reflecting why is this research important, and its feasibility. Collaborative work facilitates to exchange experiences and knowledge that help to develop the theoretical, practical and educational knowledge enabling face a world with critical thinking, acquire communication skills, tolerance, respect and willingness to listen to others, the contents are current which contributed to the development of the project effectively.